2003
DOI: 10.1002/hbm.10119
|View full text |Cite
|
Sign up to set email alerts
|

Brain activations during conscious self‐monitoring of speech production with delayed auditory feedback: An fMRI study

Abstract: Abstract:When a speaker's voice returns to one's own ears with a 200-ms delay, the delay causes the speaker to speak less fluently. This phenomenon is called a delayed auditory feedback (DAF) effect. To investigate neural mechanisms of speech processing through the DAF effect, we conducted a functional magnetic resonance imaging (fMRI) experiment, in which we designed a paradigm to explore the conscious overt-speech processing and the automatic overt-speech processing separately, while reducing articulatory mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
141
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 21 publications
10
141
2
1
Order By: Relevance
“…However, their activation is noteworthy when considered with respect to other findings. The greater right IFt response during shifted feedback is consistent with the finding of increased BOLD response in this region when auditory feedback was delayed during speech production (Hashimoto and Sakai, 2003). The IFt increase was accompanied by increased right pSTg activation.…”
Section: The Auditory Feedback Control Networksupporting
confidence: 87%
See 1 more Smart Citation
“…However, their activation is noteworthy when considered with respect to other findings. The greater right IFt response during shifted feedback is consistent with the finding of increased BOLD response in this region when auditory feedback was delayed during speech production (Hashimoto and Sakai, 2003). The IFt increase was accompanied by increased right pSTg activation.…”
Section: The Auditory Feedback Control Networksupporting
confidence: 87%
“…4A). Increased bilateral activation of posterior temporal regions during perturbation speech is consistent with previous results from studies of auditory feedback disruption, including delayed auditory feedback (Hirano et al, 1997;Hashimoto and Sakai, 2003), pitch perturbation (McGuire et al, 1996;Zarate and Zatorre, 2005;Fu et al, 2006) and noise masking (Christoffels et al, 2007) Numerous lines of evidence support the hypothesis that the expected consequences of articulation and resulting auditory feedback are compared in posterior temporal cortex (see Guenther et al, 2006 for detailed discussion). Portions of posterior left PT and lateral pSTg bilaterally have been shown to respond during both speech perception and speech production in several studies (Hickok et al, 2003;Buchsbaum et al, 2005).…”
Section: The Auditory Feedback Control Networksupporting
confidence: 84%
“…The Buchsbaum and Hickok studies indicated that these regions might be Iateralized to the left hemisphere. However, nsing delayed auditory feedback, Hashimoto and Sakai (2003) showed bilateral activation of the posterior superior temporal gyms and the inferior snpramarginal gyrus. Moreover, activity within the posterior superior temporal gyrus and superior temporal sulcus was correlated with size of the dis fluency effect caused by the DAF.…”
Section: Auditory Error Mapmentioning
confidence: 89%
“…Examples include functional magnetic resonance imaging (IMRI) studies (e.g., Ackermann, Wildgruber, Daum, & Grodd, 1998;Baciu, Abry, & Segebarth, 2000;Binder, 1997a;1997b;Binder et al, 1995;1996;Buchsbaum, Hickok, & Humphries, 2001;Buckner, Raichle, & Petersen, 1995;Buckner, Raichle, Miezin, & Petersen, 1996;Hashimoto & Sakai, 2003;Lotze, Seggewies, Erb, Grodd, & Birbaumer, 2000b;Riecker, Ackennarm, Wildgruber, Dogil, & Grodd, 2000;Rueckert et al, 1994;Urban et al, 2003;Wildgruber, Ackermann, & Grodd, 2001), positron emission tomography (PET) studies (e.g., Demone! et al, 1992;Demone!, Price, Wise, & Frackowiak, 1994;Etard et al, 2000;Fiez, Raichle, Balota, Tallal, & Petersen, 1996;Hirano et al, 1996;1997b;1997a;Mazoyer et al, 1993;Mellet, Tzourio, Denis, & Mazoyer, 1998;Papathanassiou et al, 2000;Petersen, Fox, Posner, Mintun, & Raichle, 1988;Petersen, Fox, Snyder, & Raichle, 1990;Wise, Boussaoud, Johnson, & Caminiti, 1997;Wise, Greene, Buche!, & Scott, 1999;Zatorre, Evans, Meyer, & Gjedde, 1992;Zatorre, Meyer, Gjedde, & Evans, 1996), electroencephalography (EEG) studies (e.g., Martin-Leeches, Schweinberger, & Sommer, 1997;Mills, Coffeycorina, & Neville, 1993;Neville, Coffey, Holcomb, & Tallal, 1993;van Turem10ut, Hagoort, & Brown, 1997), and magnetoencephalography (...…”
Section: Introductionmentioning
confidence: 99%
“…However, in a later study, feedback was manipulated by filtering and delaying the verbal output, which resulted in more bilateral activation of the STG [Hirano et al, 1997]. More recently, using fMRI, Hashimoto and Sakai [2003] reported more activation in the temporo-parietal regions for delayed auditory feedback conditions than for normal feedback.…”
Section: Introductionmentioning
confidence: 92%